Knowledge of conjunctivitis among high school students in Pokhara valley of Western Nepal - Tuladhar, Sarita; Gurung, Jamuna (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Conjunctivitis is a common health problem in Nepal. It is inflammation of conjunctiva presenting as red eye. It is a communicable eye disease. Health education to the students and proper management can help spread of the disease. Knowledge of conjunctivitis among school students will help in prevention of the disease. So the study was carried out to assess the knowledge of conjunctivitis among high school students in Pokhara valley of Western Nepal. Materials/ Methods: A school based cross sectional study was performed among six government schools in western Nepal from May 2019 to June 2019. Students from grade eight, nine and ten were included in the study. Data was collected using structured questionnaire including demographic data, knowledge regarding sign symptoms of conjunctivitis, treatment, prevention, complication of conjunctivitis. Data was analysed using SPSS version 11.6. Result: A total of 523 students were included in the study. The mean age of the students was 14.7 ± 1.2 years with majority of females (53%). Nearly 2/3rd of the students (61.6%) had heard of conjunctivitis. Majority of the students (87.4%) of the students mentioned that it is communicable while 80.3% of the students correctly mentioned its etiology. Majority of the students (97.9%) mentioned that it is curable with treatment as first option (97.5%). Majority of the students (98.3%) correctly responded to the preventive measures but majority of the students (83.2%) wrongly mentioned mode of transmission. Conclusion: Secondary school students in Western Nepal have poor knowledge of conjunctivitis. Appropriate eye health education should be given to school students to prevent rapid spread of infective conjunctivitis.